2017
DOI: 10.1111/birt.12310
|View full text |Cite
|
Sign up to set email alerts
|

In labor or in limbo? The experiences of women undergoing induction of labor in hospital: Findings of a qualitative study

Abstract: Conceptualizing induction as a liminal state may enhance understanding of women's feelings and promote a more woman-centered approach to care. Thorough preparation for induction, including an explanation of possible delays is fundamental to enabling women to form realistic expectations. Care providers need to consider whether women undergoing induction are receiving adequate support, analgesia, and comfort aids conducive to the promotion of physiological labor and the reduction of anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…These studies comprised a total of 277 women, of which 161 women were participants in the study by Henderson et al, 34 which was also the only mixed-methods study with a qualitative analysis of open-ended survey questions included in this review. [35][36][37][38][39][40] However, the reporting of other participant information was very inconsistent among the studies and did not allow us to synthesize the demographic characteristics of the sample. All studies addressed women's experiences of IOL in postterm pregnancy, and six studies included only primiparous women.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies comprised a total of 277 women, of which 161 women were participants in the study by Henderson et al, 34 which was also the only mixed-methods study with a qualitative analysis of open-ended survey questions included in this review. [35][36][37][38][39][40] However, the reporting of other participant information was very inconsistent among the studies and did not allow us to synthesize the demographic characteristics of the sample. All studies addressed women's experiences of IOL in postterm pregnancy, and six studies included only primiparous women.…”
Section: Resultsmentioning
confidence: 99%
“…The Australian study by Gatward et al 38 investigated primigravid women's experiences of postterm IOL with prostaglandin and found that some women felt that their body had failed, whereas others reported feelings of helplessness. 35 In the study by Gatward et al, 38 17 of 21 induced women initially feared increased interventions. 35,41 For example, Jay et al 35 recruited participants from an NHS Maternity Unit in the south of England and found that women who had expected to attend the low-risk birthing unit were disappointed to discover that this option was only available to women in spontaneous labor.…”
Section: Theme 1: Induction Requires a Shift In Expectationsmentioning
confidence: 99%
See 3 more Smart Citations